2020
DOI: 10.1186/s12889-020-8435-0
|View full text |Cite
|
Sign up to set email alerts
|

Economic burden and mental health of primary caregivers of perinatally HIV infected adolescents from Kilifi, Kenya

Abstract: Background: Eighty per cent of perinatally HIV infected (PHI) adolescents live in sub-Saharan Africa (sSA), a setting also characterized by huge economic disparities. Caregiving is crucial to the management of chronic illness such as HIV/AIDS, but the economic costs and mental disorders borne by caregivers of PHI adolescents often go unnoticed. In this study, we evaluated economic costs, coping strategies and association between economic cost and mental health functioning of caregivers of perinatally HIV infec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 34 publications
3
11
0
Order By: Relevance
“…Where resources are constrained, the required adjustments for a healthy living post an HIV-positive diagnosis (such as need for balanced diet, transport during regular clinic visits for check-up and medication refill) can be additional economic burden to persons living with HIV or their family. In fact, a recent study from this setting [ 42 ] found a high burden of both direct and indirect costs among caregivers of YLWH, with the key drivers of direct costs being transportation and medication. Additional economic burden may lead to HIV-related negative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Where resources are constrained, the required adjustments for a healthy living post an HIV-positive diagnosis (such as need for balanced diet, transport during regular clinic visits for check-up and medication refill) can be additional economic burden to persons living with HIV or their family. In fact, a recent study from this setting [ 42 ] found a high burden of both direct and indirect costs among caregivers of YLWH, with the key drivers of direct costs being transportation and medication. Additional economic burden may lead to HIV-related negative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Where resources are constrained, the required adjustments for a healthy living post an HIV-positive diagnosis (such as need for balanced diet, transport during regular clinic visits for check-up and medication re ll) can be additional economic burden to persons living with HIV or their family. In fact, a recent study from this setting [33] found a high burden of both direct and indirect costs among caregivers of YLWH, with the key drivers of direct costs being transportation and medication.…”
Section: Comparison Of Study Ndings With Previous Researchmentioning
confidence: 95%
“…Labor losses and indirect costs for HIV and HRQoL are strongly associated with severity [ 6 ]. HIV/AIDS is also associated with a significant economic burden for caregivers living with HIV [ 7 ]. Nowadays, with 1.3 million (range 970,000 to 1.6 million) HIV-positive pregnant women worldwide in 2020 [ 8 ], HIV continues to be a major global public health issue.…”
Section: Introductionmentioning
confidence: 99%